Establishing Important Criteria and Factors for Successful Integrated Information System - Ruzaini, Abdullah Arshah; Mohammad Ishak, Desa; Ab. Razak, Che Hussin (2012)
The assessment of Integrated Information Systems (IIS) is seen as an important exercise in organisation to enable the IS managers, as well as top management, to understand their return on investment in IS integration. Study has found out that very few organisations have proper assessment tool, and while other organisations have never done proper assessment to their IS integration works. Current tools on the market, however, are lack of comprehensive measures to really assess the success of IS integration in the organisation. The purpose of the paper is to provide an insight on the process of establishing important factors and criteria for successful Integrated Information System. These criteria and factors are then grouped into Integrated Information System domains which will be used as an instrument to comprehensively assess Integrated Information System in organisation. The survey process and its result are discussed and the finding shows that the survey supports the literature findings.